2004
DOI: 10.1021/la035898v
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman Investigations of Myelins in Aerosol-OT/Water System

Abstract: Surfactant outgrowth during dissolution as myelin figures, which happens on contact with water, is of prime importance in emulsification and detergency. Micro-Raman investigation of different lyotropic phases formed during dissolution of aerosol-OT (bis 2-ethylhexyl sulfosuccinate) in water during myelin formation reveals the flexible arrangement of the surfactant bilayers in myelin. The conformation around CC-CS bond and the hydrocarbon chains of aerosol-OT in the different liquid crystalline phases were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Electron micrographs [24,26] showed that each tubular myelinic figure in the egg-yolk phosphatidylcholine/water system consisted of a water core surrounded by many concentric bilayers. More recently Raman spectroscopy techniques have confirmed the concentric bilayer arrangement [1,18]. Myelinic figures are not equilibrium structures, however, and eventually break up to form vesicles or other lamellar structures.…”
Section: Pure Surfactants With Low Solubility: Myelinic Figuresmentioning
confidence: 99%
“…Electron micrographs [24,26] showed that each tubular myelinic figure in the egg-yolk phosphatidylcholine/water system consisted of a water core surrounded by many concentric bilayers. More recently Raman spectroscopy techniques have confirmed the concentric bilayer arrangement [1,18]. Myelinic figures are not equilibrium structures, however, and eventually break up to form vesicles or other lamellar structures.…”
Section: Pure Surfactants With Low Solubility: Myelinic Figuresmentioning
confidence: 99%
“…Tentative evidence for this can be found in the reported intensity variations observed in Raman spectra by Faiman et al, 99 the likely cause of which is the same molecular changes observed with increasing concentration. [102][103][104] Further support is again given by Na-AOT microemulsions that display similar behaviour. 136,137 This implies that upon increasing temperature, the Na-AOT tails adopt more kinked conformations through rotation of C-C bonds, which would explain the decrease in bilayer thickness and also result in an increase in interfacial area at high temperatures (illustrated schematically in Figure 3.14).…”
Section: Figure 39mentioning
confidence: 77%
“…Given the high degree of error and lack of any further communications regarding the observed temperature variations, the Raman spectroscopy investigation by Faiman et 103 Although the focus of this study was myelin formation in the Na-AOT system, which occurs at the lower concentrations of the lamellar region, Arunagirinathan et al also sampled within the more concentrated regions for comparison. Their experimental procedure focused the Raman laser upon the desired area of a microscope slide bearing a standard concentration gradient of Na-AOT (produced by promoting water penetration of the pure surfactant).…”
Section: Vibrational Spectroscopy and Spectrophotometrymentioning
confidence: 99%
“…The molecules adopt different conformations depending on the sample composition and will promote different packing arrangements within the bilayer, resulting in changes to the bilayer elasticity. [102][103][104][105]108 The X-ray intensities and change in the sign of the birefringence should no longer be considered as anomalous; however, these observations are still not consistent with a classical lamellar phase, and the rationalisation of the results may be significant in finally resolving the Na-AOT microstructure. In each case the observations are explained as being consistent with a lamellar phase sensitive to thermal undulations.…”
Section: Discussionmentioning
confidence: 99%
“…138 A conformational change in the Na-AOT tail region explains the more drastic changes in the SAXS patterns observed for lower concentration samples, as those of higher concentration have been reported to be comprised of predominantly one splayed conformation rather than a mixture and so will be unlikely to undergo a similar isomerisation. 103,104 Hence, the electron density distribution, and thus form factor, will not be as significantly altered at higher surfactant concentrations.…”
Section: Figure 39mentioning
confidence: 99%